Caring as temporal turns in life through creative writing - Johanna Sandbäck Forsell; Camilla Koskinen; Linda Nyholm (Nordic Journal of Arts, Culture and Health)
Aim: A person’s experience of time in life is assumed to change through suffering. This assumption developed an interest in investigating the connection between creative writing and caring, as caring may ease suffering and promote health as wholeness. The study aims to deepen the understanding of how creative writing may facilitate caring by investigating the time experience included in creative writing and its significance in relation to caring. Method: Seven hobby writers were asked to describe the meaning of creative writing in their lives. These accounts were analysed hermeneutically to gain an in-depth understanding through a dialogic process. Findings: The result show six themes: Acknowledging a childhood’s powerlessness, dealing with losses in life, capturing memories and revisiting them, building a new relationship to one’s past, living in the here and now, and being in between the past and the future. Findings suggest that caring may be viewed as temporal turns in life through creative writing, thus promoting experiences of wholeness in connection to time in life. Value: This study shows that creative writing can provide caring experiences through both the freedom of movement of the mind and by enabling a foothold in life’s temporality.